Mécanismes de Financement et Performance des IMFs en Contexte Camerounais: Une Application sur les COOPEC (Coopérative d’Epargne et de Crédit) et les IFNB (Institution Financière Non Bancaire) - Guilaire, Dadem Kemgou Edouard; Cabrel, Wafo Hilaire; Lord, Manetsa Eloge (European Scientific Journal, ESJ, 2017)
The objective of this study is to identify how the policies of financing influence the performance of Microfinance institutions (MFI). In this study, we used the MIX Market database in order to bring out information relating to the variables of financing and performance structures. The data used was obtained from eight Institutions of Microfinance in Cameroon, and were collected over a period of eight years going from 2006 to 2013. An analysis of the regressions based on a sample of 64 observations collected on 8 Cameroonian MFIs for 8 years, on the one hand, shows that the level of indebtedness also influences financial and social performance negatively